Fostering Prosocial Behavior Habits in Early Childhood through Make A Match Learning - Arisna Wahyuni; Miya Rahmawati (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Negeri Pontianak, 2026)
Prosocial behavior is one of the essential aspects of early childhood development, as it helps children build positive interactions with their surrounding environment. This study aimed to describe the findings regarding the habituation of prosocial behavior through the Make a Match learning model among early childhood students at at Pertiwi 1 Kindergarten. This research employed a qualitative approach using a case study strategy. The participants were Group B1 children aged 5-6 years. Data were collected through observations, interviews, and documentation involving the principal, teachers, and students as the research informants. The findings revealed that the Make a Match learning model effectively fostered children’s prosocial behavior through interactive and collaborative card-matching activities. The habituation of prosocial behavior was reflected in several indicators, including discipline in following the rules of the game, helping peers who encountered difficulties, caring for the environment by tidying up learning materials after use, and demonstrating care and respect toward classmates throughout the learning process. The teacher’s role as a facilitator, role model, and provider of positive reinforcement was a crucial factor in the successful habituation of these behaviors. Therefore, the Make a Match learning model can serve as an effective instructional strategy for fostering and habituating prosocial behavior in early childhood education. [Perilaku prososial merupakan salah satu aspek perkembangan penting bagi anak usia dini untuk membangun interaksi yang postif bagi lingkungan sekitarnya. Penelitian ini bertujuan untuk mengeksplorasi temuan mengenai pembiasaan perilaku prososial melalui pembelajaran make a match pada anak usia dini di TK Pertiwi I Kandangan. Penelitian ini menggunakan pendekatan kualitatif dengan strategi studi kasus. Subjek penelitian adalah anak Kelompok B1 yang berusia 5-6 tahun. Data diperoleh melalui observasi, wawancara, dan dokumentasi dengan informan yang terdiri atas kepala sekolah, guru, dan peserta didik. Hasil penelitian menunjukkan bahwa pembelajaran Make a Match mampu membiasakan perilaku prososial anak melalui kegiatan mencari pasangan kartu yang dilakukan secara berkelompok dan interaktif. Pembiasaan perilaku prososial tampak pada indikator disiplin dalam mengikuti aturan permainan, saling membantu teman yang mengalami kesulitan, peduli terhadap lingkungan dengan merapikan alat permainan setelah digunakan, serta menunjukkan sikap peduli dan menghargai teman selama proses pembelajaran. Peran guru sebagai fasilitator, pemberi teladan, dan pemberi penguatan positif menjadi faktor penting dalam keberhasilan pembiasaan tersebut. Dengan demikian, pembelajaran Make a Match dapat menjadi salah satu strategi pembelajaran yang dapat menanamkan dan membiasakan sikap perilaku prososial pada anak usia dini.]